KONSEP PERJANJIAN PERKAWINAN DI INDONESIA - Sainul, Ahmad (IAIN Padangsidimpuan, 2018)
Marriage records related to the legal consequences of national law to date still reap a lot of disagreements.The issue of unfinished marriage recording to date is about whether or not marriage is legal if not recorded. According to the conventional Islamic law based on the concepts of the Jurisprudence book that the recording of marriage is not necessary.But different in Law No.1 Year 1974 About Marriage, Government Regulation of Republic Indonesia No. 9 Year 1975 About Implementation of Act No.1 Year 1974 About Marriage Presidential Instruction No. 1 Year 1991 About Compilation of Islamic Law, and Act No.22 Year 1946 expressly Explained that every marriage should be recorded.The marriage agreement rule in Indonesiacontained in the classical jurisprudence, Law number 1 of 1974 concerning marriage (UUP) and Compilation of islamic law (KHI).